THE CREEP AND DURABILITY OF REINFORCED CONCRETE STRUCTURAL ELEMENTS - , А. А., Н. В. (Municipal economy of cities. Series: «Economy science», 2017)
One of the basic problems, which is solved on the stage design of elements of building structures design, is the analysis of stress-strain state as well as determining of lifetime. The paper is devoted to the simulation of nonlinear creep of concrete structural elements by different actions. High priority of the research theme is justified, the aim and goals are formulated. The mathematical problem statement of creep of concrete structural elements is presented. The creep problems of thin-walled structural members, which are deformities under the action of different actions varying load were solved by use of developed software. Presents a calculation example of reinforced concrete cylindrical panels. The recommendation for the rational shape design. The conclusions about the adequacy of the analysis of the reliability and durability of reinforced concrete structures. Keywords: creep, long-term strength, reinforced construction, cylindrical panel, finite element method.